2017
DOI: 10.1182/bloodadvances.2016001917
|View full text |Cite
|
Sign up to set email alerts
|

A fully recombinant human IgG1 Fc multimer (GL-2045) inhibits complement-mediated cytotoxicity and induces iC3b

Abstract: Key Points• GL-2045, a recombinant human IgG1-based Fc multimer, binds C1q and inhibits complementdependent cytotoxicity.• GL-2045 induces selflimited complement activation that is governed by both factors H and I and results in the generation of iC3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…Studies with Hexa-Fc (21) bound to a solid phase indicated full complement activation; therefore, the inhibitory activity of Fc-mTP-L309C in solution was unexpected. A similar complement inhibitory activity was most recently reported by Zhou et al (40), demonstrating that GL-2045 bound C1q, leading to generation of C4a, but limited levels of C3a and no C5a. In a second publication, the same group reported novel versions of the Stradomer with reduced binding to FcgRs but intact capability of inhibiting full complement activation (41).…”
Section: Discussionsupporting
confidence: 86%
“…Studies with Hexa-Fc (21) bound to a solid phase indicated full complement activation; therefore, the inhibitory activity of Fc-mTP-L309C in solution was unexpected. A similar complement inhibitory activity was most recently reported by Zhou et al (40), demonstrating that GL-2045 bound C1q, leading to generation of C4a, but limited levels of C3a and no C5a. In a second publication, the same group reported novel versions of the Stradomer with reduced binding to FcgRs but intact capability of inhibiting full complement activation (41).…”
Section: Discussionsupporting
confidence: 86%
“…Based on these findings, we developed a human analogue of M-045, called GL-2045, in preparation for anticipated first in human (FIH) studies and recently reported that GL-2045 inhibits complement activation in vitro (29). Here, we show that GL-2045 binds with high avidity to the low-affinity human FcγRs and interferes with the interactions of immune complexes (IC) with FcγRs.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, using a series of FcγR ‐/‐ mice, we showed that the anti‐tumor activity of mAbs targeting the costimulatory molecule, CD137, are dependent on defined Fc:FcR interactions . Such observations become even more important when taken in the context of studies from others and us showing that engagement of FcRs through multimeric Fc fusion proteins—somewhat analogous to mAb opsonization of a tumor target—have the potential to induce tolerance . Collectively, these initial insights set the stage for future investigations to determine how the interplay between Fc:FcR interactions and ligation of the target molecule influence functions.…”
Section: Introductionmentioning
confidence: 76%
“…84 Such observations become even more important when taken in the context of studies from others and us showing that engagement of FcRs through multimeric Fc fusion proteins-somewhat analogous to mAb opsonization of a tumor target-have the potential to induce tolerance. [85][86][87][88][89][90] Collectively, these initial insights set the stage for future investigations to determine how the interplay between Fc:FcR interactions and ligation of the target molecule influence functions. Furthermore, they serve as a cautionary note for researchers performing rodent studies using immunocompetent mAbs to manipulate co-signaling pathways, as these studies may have limited relevance to clinically available mAbs.…”
Section: Rational Drug Designmentioning
confidence: 99%